The recovery of alimony for the maintenance of minor children in Kazakhstan: problems of enforcement of judicial acts - Ilyassova, G.A. (KSU Publ., 2017)
The article deals with the problems related to non-performance of executive documents on recovery of alimony for the maintenance of minor children and legal measures of compulsory execution applied by bailiffs for recovering alimony. The author carried out a comparative and legal analysis of laws regulating the maintenance obligations of parents in Kazakhstan and foreign countries and the review of foreign experience on recovering alimony aimed at improving the legal mechanism on the effect on maintenance non-payers in Kazakhstan is given. As a result of the study, the author found out the reasons for the non-enforcement of judicial acts on alimony recovery for the maintenance of minor children in Kazakhstan. The effective legal measures on improving the mechanism for the recovery of alimony in order to protect the child's right to get maintenance from his parents were proposed as well.
Қазақстанда кəмелетке толмаған балаларды асырауға алименттерді өндіру: сот актілерін орындау мəселелері
Взыскание алиментов на содержание несовершеннолетних детей в Казахстане: проблемы исполнения судебных актов
Keywords: children of minority age; maintenance; maintenance obligations of parents; alimony recovery; judicial acts on alimony recovery; enforcement of judicial acts